The President's 1996 socio-economic report (Philippines : Republic of the Philippines, 1997)
The economy continued its impressive performance in 1996. The growth of national output and employment was sustained amid a decline in the inflation rate. When I assumes office in 1992, the unemployment rate was 9.8 percent; in 996, it had gone down to 8.6 percent.
Part One. The development indicators -- Part Two. The economic sectors -- Part Three. The social sectors -- Part Four. Infrastructure and technology support -- Part Five. Financing the plan.
Keywords: REPORTS -- PHILIPPINES